The Way of Saint James in the Spanish regional government websites: content analysis, orientation and predominat thematic framings - López del Ramo, Joaquín; García Marco, Francisco Javier (Revista General de Información y Documentación, 2018)
An analysis is provided of the content, orientation and predominant thematic framing of the web pages on the St James Way offered in the Spanish Regional Autonomous Governments web sites. In particular, six dimensions have been studied: basic (name, URL, autonomous community and website type), structural (location, dependency and extension), hypertextual (links, targets, downloads), interactive (support, online services, comments, social networks), informational (topics, services and other resources), and graphic and multimedia (graphic elements, framing, photography, actants and other graphic resources such as video or sound). There is a great difference among the information provided by the different portals, which correlates with the strategic importance of the Saint James Way for each regional government. The prevailing thematic frame is touristic, and the aspects of the Ways of Saint James that are emphasized are regional routes, monuments and natural surroundings. The websites have more a utilitarian or practical orientation and are less focused on providing information and documentation on the Saint James Way in itself, but this aspect is also present.
Keywords: Tourist information; Web analytics; Webgraphy; Content analysis; Graphic design; Governmental websites; Way of Saint James; Regional autonomous governments; Spain.